Perilaku Mahasiswa Mengonsumsi Sugar Sweetened Beverage (SSB) Selama Pandemi COVID-19: College Students’ Behavior Consuming Sugar-Sweetened Beverages (SSB) During the COVID-19 Pandemic - Edna Elkarima; Chrysoprase Thasya Abihail; Dicky Andhyka Priambudi; Trias Mahmudiono; Hario Megatsari; Diah Indriani; Gunawan Yoga Pratama (Universitas Airlangga, 2023)
Background: The development of Industry 4.0 makes it easy to access everything, such as food and beverages. Online food order platforms are often used among students nowadays. The COVID-19 pandemic has caused changes in purchasing behavior through online order services, especially with the policy of limiting community activities. Beverages such as boba, several types of tea, and coffee are often ordered online. Consumption for a long time and high frequency can increase body mass index, obesity, and the risk of non-communicable diseases. Objectives: This study aimed to determine the impact of the development of online ordering behavior of consuming sweet drinks (SSB) during the COVID-19 pandemic among college students in Surabaya, Indonesia. Methods: This was an observational study using a Mixed Method research design. A quantitative study with a Cross-Sectional research design and a qualitative study through an FGD was done. Results: Based on the results of the descriptive test, it was shown that tea was the most frequently purchased (daily) through online orders (12.95%). Discount greatly influences the respondents' reasons for ordering online (68.4%). Through FGD, most respondents considered promos being the biggest motivation to order. Conclusions: Currently, most 'modern' drinks are included in the SSB category. Consumption of SSB with repeated frequency for a long time will impact nutritional status. Government policies and related parties are needed to minimize the impact of SSB consumption habits, especially with the current pandemic.